The military leadership handbook - Walker, Robert William; Horn, Bernd (Canadian Defence Academy Press, 2008)
In the simplest of terms, leadership is about influencing people to achieve an objective that is important to the leader, the group, and the organization. It is the human element -- leading, motivating, and inspiring, particularly during times of crisis, chaos, and complexity when directives, policy statements, and communiques have little effect on cold, exhausted, and stressed followers. Strong leadership encourages subordinates to go beyond the obligation to obey and commit to the mission in a way that maximizes their potential. The Military Leadership Handbook is a concise and complete manual that identifies, describes, and explains all those concepts, components, and ideas that deal with, or directly relate to, military leadership. The book is a comprehensive compendium that focuses on, among other subjects, cohesion, command, cultural intelligence, discipline, fear, and trust. this applied manual provides invaluable assistance to anyone who wishes to acquire a better understanding of both the theory and application of military leadership